PEMODELAN DAN SIMULASI ANTRIAN DI KICLEANSHOES - Aliyah Alfita; Aghelia Taufani Hidianti; Arif Putra Dwiyansyah; Bimantara Yudha Sakti; Adam Alwi Nugroho; Denny Oktavina Radianto (KOLONI, 2023)
This study aims to model and simulate shoe laundry queues using computer simulation methods. Shoe laundry queue is a complex process and takes a long time to complete the washing and drying process. In this study, Anylogic simulation software was used to model and simulate shoe laundry queues using the Single Channel – Multi Phase method. There are several steps in the process of modeling and simulating shoe laundry queues. The first step is the collection of data and information regarding the queuing process, such as the number of shoes entered, the washing process time, and the drying process time, finishing process time and packing process time. The second step is to build a mathematical model that describes the queuing process. After building a mathematical model, the next step is to implement the model into Anylogic simulation software. Then data is calculated using Pom qm software to get the average number of customers and time spent in the system or queue. The simulation was performed several times to get more accurate results and to see the effect of variable changes in the queuing process. The results of this study show that by using computer simulations, optimization of the shoe laundry queue process can be carried out. By varying the washing process time, the optimal combination can be found to minimize queue time and maximize process throughput. Thus, modeling and simulating shoe laundry queues can help improve process efficiency and reduce operational costs. Keywords: queue, laundry, modeling, simulation, clean shoes